Pharmacovigilance and signal detection of adverse drug events associated with proteasome inhibitors in multiple myeloma: a real-world analysis using the FAERS database - JunYun Luo; Shupeng Chen; Meiling Zhang; Yao Gao; Yingjian Zeng (Hematology)
Background Proteasome inhibitors (PIs) such as Bortezomib, Carfilzomib, and Ixazomib have significantly improved outcomes in multiple myeloma (MM), but their real-world safety profiles require further exploration.Objective To assess adverse drug events (ADEs) associated with Bortezomib, Carfilzomib, and Ixazomib in MM patients using the FDA Adverse Event Reporting System (FAERS), and to identify new ADE signals not listed in product labels.Methods A total of 47,310 ADE reports (Bortezomib: 23,843; Carfilzomib: 9,835; Ixazomib: 13,632) were analyzed from FAERS (2004 – Q4 2024). Signal detection was conducted using Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Onset time was evaluated using Weibull survival analysis.Results All three PIs were associated with significant ADE signals across multiple system organ classes, notably in the hematologic, nervous, cardiovascular, hepatobiliary, and gastrointestinal systems. Newly identified ADEs included muscular weakness (Bortezomib), pancytopenia (Carfilzomib), and cognitive disorder (Ixazomib). Onset time analysis showed that most ADEs occurred within the first 30 days of treatment.Conclusion This study highlights both known and newly detected ADEs linked to PIs, emphasizing the importance of early-phase monitoring and ongoing pharmacovigilance. The findings provide crucial real-world evidence for clinical risk management and future label updates.